Design and properties of supramolecular elastomers. (16th October 2017) - Kajita, Takato; Noro, Atsushi; Matsushita, Yushu
Abstract: Supramolecular elastomers are supramolecular soft polymeric materials with both transient cross-links and (semi)permanent cross-links, where transient cross-links have a finite relaxation time and are typically composed of noncovalent bonds such as hydrogen bonds, metal–ligand coordination bonds, etc., whereas (semi)permanent cross-links such as covalent bonds, crystalline segments and glassy hard domains have an infinite relaxation time. Excellent elastomeric properties were induced by a combination of all the above molecular features. However, if soft polymeric materials have only supramolecular/transient cross-links with a finite relaxation time, the materials eventually flow within a finite time and cannot behave as elastomers; in other words, they are merely supramolecular polymers that have only transient cross-links or bonds. Therefore, the key to preparing higher-performance supramolecular elastomers is their molecular design. Here, we firstly review the fundamental design of supramolecular polymers to make the differences between supramolecular polymers and supramolecular elastomers clear. Second, we discuss the simultaneous incorporation of (semi)permanent cross-links and supramolecular cross-links into polymeric materials to prepare supramolecular elastomers. Finally we summarized their properties and potential applications. Graphical abstract: Highlights: Supramolecular elastomer is one of supramolecular soft polymer materials. Supramolecular elastomer has both (semi)permanent and transient cross-links. Design of supramolecular elastomers was reviewed. Mechanical properties of supramolecular elastomers were summarized.